South-South labour migration complexities and shifting visa policies in South Africa: a sociological analysis of Rhodes University academic labour migrants' perceptions - Domboka, Edward (Rhodes University, Faculty of Humanities, Department of Sociology, 2017)
International migration is an old phenomenon caused by many factors divided into push and pull factors. However, there is no enough coverage on the perceptions of the labour migrants. Although there is a vast body of writing on migration, this study delves into the experiential perceptions of academic labour migrants at Rhodes University. These academic labour migrants include professors, lecturers, researchers and postdoctoral research fellows. The study took a qualitative approach to document the experiential perceptions of academic labour migrants at Rhodes University. In-depth interviews were conducted with twelve respondents, to analyse how academic labour migrants perceive South Africa's changing visa policies in the context of regional integration and development, migration networks and choice, host-migrant relations. The study is underpinned by Probsting's (2015) concept of "spatial fix" in the context of capitalism and migration, to locate the positionality of academic labour migrants within a capitalist society. The study established that the increase in skilled labour migration is relatively linked to the expansion of capitalism. Based on the perceptions of the respondents, the study concluded that migration is inherently vital in providing cheap labour for capitalists. It established that changing visa policies is not without problems. Historical dispositions of the apartheid system, conflicting domestic versus international imperatives, neo-liberal policies and the widely condemned results of capitalism as an imperialist system and other factors influence migration management in South Africa.
Keywords: Foreign workers -- South Africa; Foreign workers -- Government policy -- South Africa; College teachers, Foreign -- South Africa -- Attitudes; College teacher mobility -- Africa; Visas -- South Africa; Rhodes University -- Employees -- Attitudes